Existence of negative dispersion and band gap in a helically inner cladded annular circular waveguide - Pandey G.N.; Thapa K.B.; Srivastava S.K.; Ojha S.P. (My University, 2025)
Helical waveguide, a different type of waveguide structure, has been considered for analysis of modal dispersion characteristics. This paper deals with the study of a new type of annular waveguide, in which the inner cladding is made by the helical windings i.e. sheath helix and the outer cladding is as usual simple step-index cladding. Using vector approach, the general characteristic equation for the proposed waveguide has been derived. The modal dispersion characteristics for the lowest order modes for different pitch angles and thickness are determined and analyzed. We have found that there is an existence of the negative dispersion curve in the helically inner cladded annular circular waveguide. It means that the inner cladding is responsible for the negative dispersion which is generally obtained in a photonic band gap. © 2010 Elsevier GmbH. All rights reserved.